Translation as Social Practice: A Case Study of the Chinese-English Translation Magazine "Renditions" - WEBER, Caterina (2021)
This thesis is a study of translation as a “socially situated activity”(Wolf and Fukari, 2007; Mason, 2014), taking as example the literary translation magazine Renditions, a biannual published by the Research Centre for Translation at the Chinese University of Hong Kong since 1973. This is a cross-disciplinary project that draws from Chinese Studies, Translation Studies and Sociology to discuss the following research question: considering that translation is widely acknowledged to involve a high amount of individual work, how do translators learn if working within a community? Building on a relatively fresh focus on the sociology of translation in Translation Studies, this thesis is also a reaction to the image of the “lone translator”(brought to attention by e.g. StAndré, 2010), which is challenged in this study of a working environment that naturally creates what educational theorist Wenger (1998) calls a “Community of Practice (CoP)”. The subject is tackled from four interconnected and mutually defining perspectives on the social learning process, as proposed by Wenger: learning by experience (meaning), by doing (practice), by belonging (community), and by becoming (identity). Some related literature (Mason, 2014) suggests that these same four points correspond to the way translators learn. I argue that, even though the activity of translating does indeed involve a considerable amount of individual work, the image of the “lone translator” fades once translators are seen as individuals participating in a community that has an impact on their professional activity. The magazine chosen as the source of material for this project, Renditions, is a relevant and interesting object of study for several reasons. To date, little attention has been paid to literary journals and magazines, partly because their contents are not homogeneous, which makes any attempt at a systematic assessment and study of such a subject “a formidable task” (Gimpel, 1999). For a study focusing on the sociology of translation, however, a magazine is an ideal example of CoP where translators network, collaborate, and re-consider their work in the light of this social contact. Also, given that translation is essentially practice-based,focusing on a magazine allowed me to turn directly to some of Renditions’ many contributors for information: methods used include semi-structured interviews and textual analysis of examples from Renditions’ catalogue. This case study shows that translators tend to benefit professionally from interaction with a CoP; that translation involves a perpetual kind of learning process; that the format of a translation magazine makes translation more visible, highlighting a profession that has been criticised as invisible (see Venuti, 1995); that magazines may be difficult material to research systematically in terms of contents, but suggest themselves as suitable for the study of naturally occurring CoPs.